Arguments about Responsibility to Protect in Latin America: Diversity and Controversy about the Application of the Norm - Salgado Espinoza, Raúl (2018)
This paper analyzes how the international norm of Responsibility to Protect (R2P) is conceived in the south of the American continent, paying special attention to the position of Ecuador and Brazil, and explains the different South American perspectives about its application in the cases of Syria and Libya. This article takes into consideration the constructivist theory to deepen in evidences of discursive character understand and explain how a posture about a liberal norm is built from South. According to constructivism a qualitative methodology was used, studying academic literature about the subject, analyzing official speeches from Ministers and Presidents of the study cases and interpreting journalistic notes and official documents from Brazil and Ecuador.